The Leadership Of The Head Of The Study Program In Efforts To Improve Lecturer Performance - Sopian, Adi; S, Usanto; Sauri, R. Supyan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Higher education is a critical sector in the advancement of a nation, and the caliber of instruction provided within this domain is predominantly dictated by the effectiveness of lecturers. Enhancing the performance of lecturers has the potential to elevate both the standard of education and instruction. In order for educational institutions to attain commendable benchmarks for performance and eligibility, they must be guided by a Head of Study Program who possesses thorough expertise in the field of leadership. Data for this study were collected via direct interviews with the Head of the Study Program and indirect and direct observation. The findings of this study indicate that the Head of the Business Study Program at Swadarma Institute of Technology has implemented various strategies to enhance lecturer performance. Among these is the provision of professional development opportunities, including workshops, training, and mentoring, which assist lecturers in refining their teaching abilities and remaining current with the most recent trends and optimal methodologies.